Statins: a tale of two pathways—cardiovascular savior, renal ineffectual - Jihyun Yang (Precision and Future Medicine)
Statins are effective in improving outcomes in the general population. However, in patients with chronic kidney disease (CKD), clinical outcomes and therapeutic approaches require careful interpretation from multiple perspectives. Managing dyslipidemia in CKD presents unique challenges requiring a comprehensive understanding of alterations in lipid metabolism in renal dysfunction. This review explored the key factors influencing statin efficacy, safety, and guideline recommendations in the CKD population, with a focus on lipid-lowering strategies tailored to renal function.